2001
DOI: 10.1038/sj.ijo.0801783
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pedometer-determined ambulatory activity and body composition variables

Abstract: OBJECTIVE: To examine the relationship between pedometer-determined ambulatory activity (steps=day) and body composition variables body mass index (BMI) and percentage body fat). DESIGN: Secondary analysis of a cross-sectional objective activity monitoring study for up to 21 consecutive days. SUBJECTS: A total of 109 apparently healthy adults (eight African American males, 23 African-American females, 33 Caucasian males, 45 Caucasian females), age 44.9 AE 15.8 y, BMI ¼ 26.9 AE 5.1 kg=m 2 . MEASUREMENTS: Pedome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 43 publications
13
113
1
4
Order By: Relevance
“…5,8,20,21 The step counts observed in the current study are also similar to those observed in a recent study using Finish adults, 22 in which a control group, continuing with their normal daily routine, reported a mean daily step count of approximately 9500 steps/day. 22 Using data from the National Health and Nutrition Examination Survey (NHANES), in 2002 the prevalence of obesity in the US was reported to be 30.6%, 23 in comparison with the 24% obesity prevalence seen in UK adults in 2004.…”
Section: Discussionsupporting
confidence: 88%
“…5,8,20,21 The step counts observed in the current study are also similar to those observed in a recent study using Finish adults, 22 in which a control group, continuing with their normal daily routine, reported a mean daily step count of approximately 9500 steps/day. 22 Using data from the National Health and Nutrition Examination Survey (NHANES), in 2002 the prevalence of obesity in the US was reported to be 30.6%, 23 in comparison with the 24% obesity prevalence seen in UK adults in 2004.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, step rate in overweight and obese individuals was lower than normal-weight individuals and there was a significant correlation between BMI and step rate (r ¼ À0.093; P ¼ 0.009). Lower BMI in individuals whose step rates are o6000, 33 lower step rate in obese 34 and the negative correlation [33][34][35][36] were also reported in North American.…”
Section: Physical Activity and Obesity M Yoshioka Et Almentioning
confidence: 52%
“…To our knowledge, no information is available from thoroughly examining the relationship between BMI or body composition, i.e. FFM index (FFMI, FFM divided by height squared), FM index (FMI, FM divided by height squared) or body fat percentage (%BF) and physical activity in adult women, particularly in Asian populations.Recently, many cross-sectional studies on adult women in Western countries and Japan reported that BMI and %BF were inversely associated with daily walking steps (9,10) . Furthermore, %BF was negatively associated with the duration of vigorous-intensity physical activity assessed by accelerometry (11) .…”
mentioning
confidence: 99%